Extracellular IgC2 constant domains of CEACAMs mediate PI3K sensitivity during uptake of pathogens. - Maike Voges; Verena Bachmann; Jan Naujoks; Kathrin Kopp; Christof R Hauck (PLoS ONE, 2012)
Several pathogenic bacteria utilize receptors of the CEACAM family to attach to human cells. Binding to different members of this receptor family can result in uptake of the bacteria. Uptake of Neisseria gonorrhoeae, a gram-negative human pathogen, via CEACAMs found on epithelial cells, such as CEACAM1, CEA or CEACAM6, differs mechanistically from phagocytosis mediated by CEACAM3, a CEACAM family member expressed selectively by human granulocytes.We find that CEACAM1- as well as CEACAM3-mediated bacterial internalization are accompanied by a rapid increase in phosphatidylinositol-3,4,5 phosphate (PI(3,4,5)P) at the site of bacterial entry. However, pharmacological inhibition of phosphatidylinositol-3' kinase (PI3K) selectively affects CEACAM1-mediated uptake of Neisseria gonorrhoeae. Accordingly, overexpression of the PI(3,4,5)P phosphatase SHIP diminishes and expression of a constitutive active PI3K increases CEACAM1-mediated internalization of gonococci, without influencing uptake by CEACAM3. Furthermore, bacterial uptake by GPI-linked members of the CEACAM family (CEA and CEACAM6) and CEACAM1-mediated internalization of N. meningitidis by endothelial cells require PI3K activity. Sensitivity of CEACAM1-mediated uptake toward PI3K inhibition is independent of receptor localization in cholesterol-rich membrane microdomains and does not require the cytoplasmic or the transmembrane domain of CEACAM1. However, PI3K inhibitor sensitivity requires the Ig(C2)-like domains of CEACAM1, which are also present in CEA and CEACAM6, but which are absent from CEACAM3. Accordingly, overexpression of CEACAM1 Ig(C2) domains blocks CEACAM1-mediated internalization.Our results provide novel mechanistic insight into CEACAM1-mediated endocytosis and suggest that epithelial CEACAMs associate in cis with other membrane receptor(s) via their extracellular domains to trigger bacterial uptake in a PI3K-dependent manner.